ANALISIS KUALITATIF DAN KUANTITATIF MINYAK ATSIRI DAUN CENDANA (Santalum album L.) - Alfonsa Theresia Sujaya; Sajekti Palupi; Alfian Hendra Krisnawan (CALYPTRA, 2020)
Santalum album L (Cendana ) is a plant has many benefits that grow a lot in Indonesia. Already done research on the roots and stems of the cendana plant, but not research on the leaf. In this reseacrh, the volatile component from of the leaf of this plant was analyzed in qualitative and quantitative. For qualitative analysis are organoleptic observations, the determination of the refractive index, spesific gravity, profile Thin Layer Chromatography (TLC), profile gas chromatography and mass spectra (GC-MS). Quantitative analysis performed assay of essential oil with stahl distillation method. Santalum album’s essential oil has a clear liquid, the color is brown, has a very fragrant aroma and taste is a little bit bitter. The spesific gravity of the essential oil is 1,28±0,021, the refractive index is 1,46±0,01 and the total content is 0,6±5,03ൈ10-5(v/w). profileTLC revealed that there are 4 spot. The result GC-MS showed there were 6 components, and the highest component is Pyrrolidine 1-(ethyl-1-cyclohexen-1-yl).